Fibrous dysplasia: rapid malignant transformation into osteogenic sarcoma - A rare occurance - Gon, S; Majumdar, B; Bhattacharyya, A; Bhattacharya, RN (Journal of Pathology of Nepal, 2012)
Malignant transformation of fibrous dysplasia is rare, occurring in less than 1% of cases with a mean lag period of 13.5 years. We report a case of Osteogenic Sarcoma with chondroid differentiation in a pre-existing Fibrous Dysplasia occurring within one year of surgical resection and without any history of exposure to radiation. To the best of our knowledge and extensive search of literature, malignant transformation of Fibrous Dysplasia in such a short period of time, and without history of radiation exposure has never been reported from India. Journal of Pathology of Nepal (2012) Vol. 2, 335-337 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6891